Vancouver Transcatheter Aortic Valve Replacement Clinical Pathway: Minimalist Approach, Standardized Care, and Discharge Criteria to Reduce Length of Stay. (May 2016) - Lauck, Sandra B.; Wood, David A.; Baumbusch, Jennifer; Kwon, Jae-Yung; Stub, Dion; Achtem, Leslie; Blanke, Philipp; Boone, Robert H.; Cheung, Anson; Dvir, Danny; Gibson, Jennifer A.; Lee, Bobby; et al.
Abstract : We describe the development, implementation, and evaluation of a standardized clinical pathway to facilitate safe discharge home at the earliest time after transfemoral transcatheter aortic valve replacement. Between May 2012 and October 2014, the Heart Team developed a clinical pathway suited to the unique requirements of transfemoral transcatheter aortic valve replacement in contemporary practice. The components included risk-stratified minimalist periprocedure approach, standardized postprocedure care with early mobilization and reconditioning, and criteria-driven discharge home. Our aim was to reduce variation in care, identify a subgroup of patients suitable for early discharge (⩽48 hours), and decrease length of stay for all patients. We addressed barriers related to historical practices, complex multidisciplinary stakeholder engagement, and adoption of length of stay as a quality indicator. We retrospectively reviewed the experiences of 393 consecutive patients; 150 (38.2%) were discharged early. At baseline, early discharge patients had experienced less previous balloon aortic valvuloplasty, had higher left ventricular ejection fraction, better cognitive function, and were less frail than the standard discharge group (>48 hours). Early discharge was associated with the use of local anesthesia, implantation of balloon expandable device, avoidance of urinary catheter, and early removal of temporary pacemaker. Median length of stay was 1 day for early discharge and 3 days for other patients; 97.7% were discharged home. There were no differences in 30-day mortality (1.3%), disabling stroke (0.8%), or readmission (10.7%). The implementation of a transcatheter aortic valve replacement clinical pathway shifted the program's approach to combine standardized processes and individual risk stratification. The Vancouver transcatheter aortic valve replacement clinical pathway requires a rigorous assessment to determine its efficacy, safety, and reproducibility.